"Character Weaknesses" and "Fruit Machines": Towards an Analysis of The Anti-Homosexual Security Campaign in the Canadian Civil Service - Kinsman, Gary (Labour / Le Travail, 1995)
This investigation interrogates State documents that were part of organizing the anti-homosexual security campaign in the late 1950s and 19605 in the Canadian civil service that led to hundreds of men and women being dismissed and transferred from their jobs. This critical analysis provides an entry point into the textually-mediated social organization of this security campaign. Crucial to this were ideological conceptualizations of `national security' and 'character weakness' that were used to mandate practices of surveillance, dismissal, and transfer. This security campaign led to the identification of thousands of suspected gay men and lesbians that moved far beyond the civil service; to state-funded research on identifying homosexuals called the 'fruit machine'; to debates within the security regime over how broad-ranging this campaign should be; and to non-cooperation from lesbians and gay men.
Keywords: Canada; Civil service; LGBT people; National security; POLITICAL campaigns; PUBLIC service employment; SLOT machines